The transculturality of 'gut feelings'. Results from a French Delphi consensus survey. (December 2013) - Le Reste, Jean-Yves; Coppens, Magali; Barais, Marie; Nabbe, Patrice; Le Floch, Bernard; Chiron, Benoît; Dinant, Geert Jan; Berkhout, Christophe; Stolper, Erik; Barraine, Pierre
Abstract Background: General Practitioners (GPs) sometimes base their clinical decisions on 'gut feelings.' Research into the significance of this phenomenon with focus groups and a Delphi consensus procedure in the Netherlands provided a concept of 'gut feelings:' a sense of alarm, a sense of reassurance and several determinants. The transculturality of 'gut feelings' has been examined briefly until now as the issue is complex. Objective: To determine whether a consensus on 'gut feelings' in general practice in France could be obtained. Using a similar Delphi consensus procedure and the same six initial statements as in the Netherlands, and compare the French results with the seven final Dutch consensual statements. Method: Qualitative research, including a Delphi consensus procedure after a forward-backward translation (FBT) of the initial Dutch statements of 'gut feelings.' A heterogeneous sample of 34 French expert GPs participated. FBT of the final French statements was undertaken for a content comparison with the Dutch. Results : After three Delphi rounds, French GPs reached agreement on nine statements. Many similarities have been found between the Dutch and the French defining statements, with reservations concerning the 'sense of reassurance, ' which French GPs seemed to feel more cautious about. Conclusion: 'Gut feelings' are a well-defined concept in France too. The Dutch and the French consensual statements seem very close. The transculturality of the concept is confirmed, which is a new indicator that 'gut feelings' are a self-contained concept.